Effectiveness of the 'Mesiodistal Guide Set' in Dental Implant Placement: A Clinical Trial - Mansouri, Zahra; Amid, Reza; Karami, Daryoush; Mehrani Sabet, Javad; Cheraghi, Negin (Journal of Dental School, 2024)
Objectives This study used a newly designed mesiodistal guide set to assess and compare the precision of the mesiodistal positioning of dental implants relative to adjacent teeth. The cost-effective and convenient guide set was compared to the conventional freehand surgery technique in partially edentulous patients. Methods The study enrolled 38 patients requiring at least one implant. Participants were divided into case and control groups, receiving 30 implants in each group: 10 in free-end areas, and 20 in single-tooth edentulous spaces. In the case group, implants were placed using the mesiodistal guide set, while the control group underwent the freehand procedure. The postoperative evaluation involved taking parallel periapical radiographs to measure distances and angles between the implants and adjacent teeth using Photoshop CS4. The data was rigorously analyzed using the Generalized Estimating Equations (GEE) method, a statistical technique for modeling clustered data, with statistical significance set at p<0.05. Results Measurements of the mesiodistal distances between implants and adjacent teeth showed reduced deviations in the case group, with statistically significant differences in mesial (P=0.001) and distal (P=0.036) distances. The tooth-supported area exhibited better outcomes compared to the free-end area. However, there were no significant differences in implant-tooth angulation, whether mesial (P=0.503) or distal (P=0.188). Conclusion The study indicated that the mesiodistal guide set offers practical guidance for positioning implants next to teeth in partially edentulous patients. This finding has significant practical implications, providing tangible evidence for the clinical application of the guide set. Despite some limitations, the findings fall within clinically acceptable parameters, and the guide set proved to enhance accuracy over the freehand method.